2007
DOI: 10.1073/pnas.0704533104
|View full text |Cite
|
Sign up to set email alerts
|

Correlated network activity enhances synaptic efficacy via BDNF and the ERK pathway at immature CA3–CA1 connections in the hippocampus

Abstract: At early developmental stages, correlated neuronal activity is thought to exert a critical control on functional and structural refinement of synaptic connections. In the hippocampus, between postnatal day 2 (P2) and P6, network-driven giant depolarizing potentials (GDPs) are generated by the synergistic action of glutamate and GABA, which is depolarizing and excitatory. Here the rising phase of GDPs was used to trigger Schaffer collateral stimulation in such a way that synchronized network activity was coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 45 publications
4
84
0
Order By: Relevance
“…As in other forms of developmental plasticity (Gaiarsa et al, 2002;Kasyanov et al, 2004;Mohajerani et al, 2007), calcium entering into the cell through VDCCs was responsible for positive changes in synaptic efficacy as demonstrated by the lack of STD-LTP when BAPTA was present in the recording pipette or when nifedipine was added to the extracellular solution. In accord to the calcium hypothesis, the direction of synaptic changes would be determined by distinct calcium signals which would activate different molecular pathways (Caporale and Dan, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As in other forms of developmental plasticity (Gaiarsa et al, 2002;Kasyanov et al, 2004;Mohajerani et al, 2007), calcium entering into the cell through VDCCs was responsible for positive changes in synaptic efficacy as demonstrated by the lack of STD-LTP when BAPTA was present in the recording pipette or when nifedipine was added to the extracellular solution. In accord to the calcium hypothesis, the direction of synaptic changes would be determined by distinct calcium signals which would activate different molecular pathways (Caporale and Dan, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…One attractive candidate is BDNF, which can be released in a calciumdependent way by depolarization of the postsynaptic cell (Goodman et al, 1996;Lessmann et al, 2003;Magby et al, 2006;Kuczewski et al, 2008b). Previous studies from the immature hippocampus have shown that BDNF is the retrograde messenger required for increasing the probability of GABA and glutamate release at GABAergic and glutamatergic synapses, respectively (Gubellini et al, 2005;Mohajerani et al, 2007). Therefore, we tested whether BDNF was able to mimic the effects of STD-LTP on MF-evoked GPSCs.…”
Section: Pairing-induced Synaptic Potentiation Requires the Activatiomentioning
confidence: 99%
“…these glutamatergic synapses (Mohajerani et al, 2007). Therefore, the observed decrease in coincident activity in Nkcc1 Ϫ/Ϫ hippocampus might change glutamatergic transmission between the Schaffer collaterals and CA1 neurons.…”
Section: Delayed Maturation Of Glutamatergic and Gabaergic Transmissimentioning
confidence: 94%
“…Neurotrophins may be key in the development of depression (13); BDNF, for instance, can activate intracellular mitogen-activated protein kinase/extracellular signal-regulated kinase cascade signaling pathways (14), affecting synaptic plasticity (12) and alleviating the symptoms of depression (15), and BDNF may thus be important in the maintenance of emotional stability. Deletion of the BDNF receptor induces a reduction in neurogenesis and increases anxious behavior (16).…”
Section: Introductionmentioning
confidence: 99%